GUIDELINES FOR DEVELOPING LEADERSHIP IN THE DIGITAL ERA FOR SCHOOL ADMINISTRATORS UNDER THE MAE HONG SON PRIMARY EDUCATIONAL SERVICE AREA OFFICE, AREA 2 - Pairot, Pimsamai; Thongkumpong, Sunat; Chumchoei, Sirikorn (Journal of MCU Nakhondhat, 2024)
This research The objectives are 1) To study the leadership in the digital age of educational institution administrators. Under the Mae Hong Son Primary Educational Service Area Office, Area 2 2) To find ways to develop leadership in the digital age of educational institution administrators. Under the Mae Hong Son Primary Educational Service Area Office, Areas 2 and 3) To assess the appropriateness and feasibility of the guidelines for developing leadership in the digital age of educational institution administrators under the Mae Hong Son Primary Educational Service Area Office, Area 2. Research study This uses a survey research method. The sample group and data sources used in this research include educational institution administrators. Under the Mae Hong Son Primary Educational Service Area Office, Area 2, there were 92 people. Data were analyzed by looking for percentage, frequency, mean, and standard deviation. and content analysis. The research results found that the leadership in the digital age of educational institution administrators There is a high level of practice. Guidelines for developing leadership in the digital era for school administrators found that having a digital vision It should play a role in inspiring personnel to understand the technology vision. Management using information Should be a leader in technology by studying the correct use of technology by exchanging knowledge until becoming skilled in using technology. Promoting the use of technology in teaching and learning There should be a plan for the use of digital technology in teaching and learning. and having ethics in the use of information technology Policies should be established to raise awareness of the relationship between digital technology and ethics. privacy and safety and the results of the evaluation of suitability and feasibility were found to be at the highest level of suitability. and there is a high level of possibility